A rare case of Clostridium paraputrificum bloodstream infection in a patient with intestinal necrosis: case report and literature review - Ji, Caixia; Wang, Ke; Chen, Zongyao; Jianfei, E.; Jiang, Yayun; Huang, Ziqian; Huang, Wei (Frontiers in Medicine, 2025)
Bloodstream infections caused by anaerobic bacteria present a serious threat to patients. Rapid and accurate diagnosis is crucial for treatment and patient prognosis. Herein, we report a rare case of Clostridium paraputrificum bacteremia in an 82-year-old woman who developed an infection after undergoing necrotic small bowel resection. The patient was treated with 5-day anti-infective therapy with meropenem and linezolid, successfully controlling the disease. We also constructed a phylogenetic tree with other similar bacteria using gene sequencing and showed the virulence and antimicrobial resistance of C. paraputrificum. Additionally, the clinical features and antibiotic treatment of this case were reviewed and discussed in the existing literature. This case and review illustrate the insidious nature of C. paraputrificum infections, emphasizing the need for greater clinician awareness and improved diagnostic and treatment strategies.